Molybdenum cofactor deficiency: Identification of a patient with homozygote mutation in the MOCS3 gene. Issue 6 (25th May 2017) - Huijmans, Jan G. M.; Schot, Rachel; de Klerk, Johannis B. C.; Williams, Monique; de Coo, René F. M.; Duran, Marinus; Verheijen, Frans W.; van Slegtenhorst, Marjon; Mancini, Grazia M. S.
Abstract : We describe the clinical presentation and 17 years follow up of a boy, born to consanguineous parents and presenting with intellectual disability (ID), autism, "marfanoid" dysmorphic features, and moderate abnormalities of sulfite metabolism compatible with molybdenum cofactor deficiency, but normal sulfite oxidase activity in cultured skin fibroblasts. Genomic exome analysis revealed a homozygous MOCS3 missense mutation, leading to a p.Ala257Thr substitution in the highly conserved ubiquitin‐like‐domain of the protein. MOCS3 is the third protein, besides MOCS1 and MOCS2, involved in the biosynthesis of the molybdenum cofactor and has a dual ubiquitin‐like function in tRNA thiolation. It is plausible that the phenotype results from deficiency of this dual function, not only from defective synthesis of molybdenum cofactor, which would explain similarities and differences from the MOCS1 and MOCS2‐related disorders. This observation should encourage testing of additional ID patients with mild abnormalities of sulfite metabolism for MOCS3 mutations.